Effects of Goal Management Training on self-efficacy, self-esteem, and quality of life for persons with schizophrenia spectrum disorders - Øie, Marie Bjørntvedt; Haugen, Ingvild; Stubberud, Jan; Øie, Merete Glenne (Frontiers in Psychology, 2024)
Persons with schizophrenia often show executive dysfunction assessed with both subjective (self-report) and objective (neuropsychological tests) measures. In a recent randomized controlled trial (RCT), subjective executive functioning in everyday life was improved following Goal Management Training (GMT). The aim of the current study is to investigate the potential of GMT to improve secondary well-being outcomes from that RCT, including self-esteem, self-efficacy, and quality of life in persons with schizophrenia spectrum disorders. Since well-being is frequently lower in persons with schizophrenia compared to healthy individuals, further knowledge about well-being as an outcome after cognitive remediation may have implications for clinical treatment. Sixty-five participants were randomly assigned to GMT (n = 31) or a waiting list control condition (n = 34). Assessments were conducted at baseline (T1), immediately after the intervention (T2–5 weeks), and at six-month follow-up (T3). Measures included the Rosenberg Self-Esteem Scale, the Perceived Quality of Life Scale, and the General Self-Efficacy Scale. Results were analyzed using a linear mixed model analysis for repeated measures. There were no significant effects of GMT on self-esteem or quality of life. Only the GMT group showed a significant increase in self-efficacy that was most evident at six months follow-up, F(1, 34) = 10.71, p = 0.002, d = 0.71. Improved self-efficacy was found to correlate significantly with a reduction in perceived executive dysfunction in an exploratory post hoc analysis. Our findings demonstrate the potential of GMT in improving self-efficacy in schizophrenia Clinical trial registration:https://clinicaltrials.gov, NCT03048695.